Effectiveness of Teacher and Student Communication in Improving Student Achievement in Junior High School - Nursyamsi, Nursyamsi; Alinurdin, M (Jurnal Konsepsi, 2024)
This study aims to determine the importance of communication in the learning process of subjects at SMP Negeri 2 Maros. This study uses a quantitative and qualitative research design. The population of this study was 14 teachers and 209 students. Data collection techniques used are observation, interviews, and questionnaires. Researchers combine several kinds of data analysis techniques. Quantitative data were analyzed statistically. For qualitative data is classified in the form of focus groups and becomes accurate facts. The results showed that interaction or communication between teachers and students at SMP Negeri 2 Maros combines various methods in teaching activities to create a productive educative atmosphere.